Impulse control disorders in Parkinson’s disease: recent advances - Voon, Valerie (2011)
PURPOSE OF REVIEW: To review the recent advances in the epidemiology and pathophysiology of impulse control disorders (ICD) in Parkinson’s disease (PD). RECENT FINDINGS: Large cross-sectional and case-control multicentre studies show that ICDs in PD are common with a frequency of 13.6%. These behaviours are associated with impaired functioning and with depressive, anxiety and obsessive symptoms, novelty seeking and impulsivity. Behavioural subtypes demonstrate differences in novelty seeking and impulsivity suggesting pathophysiological differences. Observational and neurophysiological studies point towards a potential mechanistic overlap between the behavioural (ICDs) and motor (dyskinesias) dopaminergic sequelae. Converging data suggest dopamine agonists in ICDs appear to enhance learning from rewarding outcomes and impulsive choice. ICD patients also have enhanced risk preference and impaired working memory. Neuroimaging data points towards enhanced bottom-up ventral striatal dopamine release to incentive cues, gambling tasks and reward prediction, and possibly inhibition of top-down orbitofrontal influences. Dopamine agonist-related ventral striatal hypoactivity to risk is consistent with impaired risk evaluation. SUMMARY: Recent large scale studies and converging findings are beginning to provide an understanding of mechanisms underlying ICDs in PD which can guide prevention of these behaviours and optimize therapeutic approaches.